Penicillium janthinellum NCIM1366 shows improved biomass hydrolysis and a larger number of CAZymes with higher induction levels over Trichoderma reesei RUT-C30 - Sreeja-Raju, Athiraraj; Christopher, Meera; Kooloth-Valappil, Prajeesh; Kuni-Parambil, Rajasree; Gokhale, Digambar Vittal; Sankar, Meena; Abraham, Amith; Pandey, Ashok; Sukumaran, Rajeev K. (Biotechnology for Biofuels, 2020)
Background Major cost of bioethanol is attributed to enzymes employed in biomass hydrolysis. Biomass hydrolyzing enzymes are predominantly produced from the hyper-cellulolytic mutant filamentous fungus Trichoderma reesei RUT-C30. Several decades of research have failed to provide an industrial grade organism other than T. reesei, capable of producing higher titers of an effective synergistic biomass hydrolyzing enzyme cocktail. Penicillium janthinellum NCIM1366 was reported as a cellulase hyper producer and a potential alternative to T. reesei, but a comparison of their hydrolytic performance was seldom attempted. Results Hydrolysis of acid or alkali-pretreated rice straw using cellulase enzyme preparations from P. janthinellum and T. reesei indicated 37 and 43% higher glucose release, respectively, with P. janthinellum enzymes. A comparison of these fungi with respect to their secreted enzymes indicated that the crude enzyme preparation from P. janthinellum showed 28% higher overall cellulase activity. It also had an exceptional tenfold higher beta-glucosidase activity compared to that of T. reesei, leading to a lower cellobiose accumulation and thus alleviating the feedback inhibition. P. janthinellum secreted more number of proteins to the extracellular medium whose total concentration was 1.8-fold higher than T. reesei. Secretome analyses of the two fungi revealed higher number of CAZymes and a higher relative abundance of cellulases upon cellulose induction in the fungus. Conclusions The results revealed the ability of P. janthinellum for efficient biomass degradation through hyper cellulase production, and it outperformed the established industrial cellulase producer T. reesei in the hydrolysis experiments. A higher level of induction, larger number of secreted CAZymes and a high relative proportion of BGL to cellulases indicate the possible reasons for its performance advantage in biomass hydrolysis.
Keywords: Bioethanol; CAZymes; Cellulase; Penicillium janthinellum; Secretome; Trichoderma reesei

Lignocellulose degradation by Penicillium janthinellum enzymes is influenced by its variable secretome and a unique set of feedstock characteristics - Christopher, Meera; Sreeja-Raju, Athiraraj; Sankar, Meena; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Bioresource Technology, 2022)
Substrate characteristics and proteins that affect lignocellulose-hydrolysis by the hypercellulolytic fungus Peni-cillium janthinellum NCIM 1366 (PJ-1366) were investigated. The hydrolysis rate of PJ-1366 enzymes was very high, with upto 75 % of the reaction being completed in initial 4 h. Comparison of the hydrolytic efficiencies on differently pretreated biomass indicated that the greatest (negative) effect was imparted by lignin, suggesting that improving ligninase activity of the PJ-1366 enzymes may help to improve hydrolysis. Larger pore sizes and higher crystallinity of substrates, which favor enzyme penetration and processive hydrolysis, positively influ-enced hydrolysis efficiency. For alkali-pretreated substrates, 16 FPU/g of PJ-1366 cellulases released the sugar -equivalent of using 10 FPU/g of a commercial biomass hydrolyzing enzyme. By correlation analysis, 41 proteins, including 20 CAZymes were identified, whose abundance in the secretome positively correlated with the cellulase activities of the culture filtrate. These proteins may be considered as the primary drivers of FPase/ CMCase/pNPGase/xylanase activity in PJ-1366.
Keywords: Biofuel; CAZyme; Cellulase; Penicillium; Secretome

Machine learning-based approach to determine infection status in recipients of BBV152 (Covaxin) whole-virion inactivated SARS-CoV-2 vaccine for serological surveys - Singh, Prateek; Ujjainiya, Rajat; Prakash, Satyartha; Naushin, Salwa; Sardana, Viren; Bhatheja, Nitin; Singh, Ajay Pratap; Barman, Joydeb; Kumar, Kartik; Gayali, Saurabh; Khan, Raju; Rawat, Birendra Singh; et al. (Computers in Biology and Medicine, 2022)
Data science has been an invaluable part of the COVID-19 pandemic response with multiple applications, ranging from tracking viral evolution to understanding the vaccine effectiveness. Asymptomatic breakthrough infections have been a major problem in assessing vaccine effectiveness in populations globally. Serological discrimination of vaccine response from infection has so far been limited to Spike protein vaccines since whole virion vaccines generate antibodies against all the viral proteins. Here, we show how a statistical and machine learning (ML) based approach can be used to discriminate between SARS-CoV-2 infection and immune response to an inactivated whole virion vaccine (BBV152, Covaxin). For this, we assessed serial data on antibodies against Spike and Nucleocapsid antigens, along with age, sex, number of doses taken, and days since last dose, for 1823 Covaxin recipients. An ensemble ML model, incorporating a consensus clustering approach alongside the support vector machine model, was built on 1063 samples where reliable qualifying data existed, and then applied to the entire dataset. Of 1448 self-reported negative subjects, our ensemble ML model classified 724 to be infected. For method validation, we determined the relative ability of a random subset of samples to neutralize Delta versus wild-type strain using a surrogate neutralization assay. We worked on the premise that antibodies generated by a whole virion vaccine would neutralize wild type more efficiently than delta strain. In 100 of 156 samples, where ML prediction differed from self-reported uninfected status, neutralization against Delta strain was more effective, indicating infection. We found 71.8% subjects predicted to be infected during the surge, which is concordant with the percentage of sequences classified as Delta (75.6%-80.2%) over the same period. Our approach will help in real-world vaccine effectiveness assessments where whole virion vaccines are commonly used.
Keywords: BBV152; Covaxin; COVID-19; Ensemble methods; Infection; machine learning; SARS-CoV-2

Cellulase hyper-producing fungus penicillium janthinellum NCIM 1366 elaborates a wider array of proteins involved in transport and secretion, potentially enabling a diverse substrate range - Christopher, Meera; Sreeja-Raju, Athiraraj; Kooloth-Valappil, Prajeesh; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioenergy Research, 2023)
The efficient breakdown of lignocellulose requires the concerted activity of multiple enzymes. Previous studies on Penicillium janthinellum NCIM 1366 (PJ-1366) have revealed a more versatile repertoire of cellulases as compared to the hypercellulolytic strain Trichoderma reesei RUT-C30. Since a robust transport and secretion network is necessary to achieve proficient enzyme production, the transporters and extracellular proteins of PJ-1366 identified from its genome data were compared with those of Penicillium rolfsii (the phylogenetically closest species) and T. reesei RUT-C30 (the industrial work horse for cellulase production). Transmembrane proteins formed 20.4%, 21.0% and 18.2%, respectively of the proteome of PJ-1366, P. rolfsii and T. reesei RUT-C30, and 292 of them were mapped as transporters in PJ-1366. Major facilitator superfamily transporters (264) and sugar transporters (167) are abundant in PJ-1366, which probably aid in the uptake of oligosaccharide inducers of cellulase. The number of extracellular proteins (1007) in PJ-1366 is the highest reported for a Penicillium species. Also, PJ-1366 encoded 1.5 x more proteins involved in carbohydrate metabolism than the other fungi, and its secreted CAZymes belonged to much more diverse families (73), potentially enabling the fungus to act on heterogenous substrates. Structural differences in some untranslated protein response (UPR) effectors like Pdi and Clx detected in PJ-1366 may facilitate unique modes of cellulase regulation.
Keywords: Cellulase; Pathway; Penicillium; regulation; Secretion; Transport

Comparison of the solid-state and submerged fermentation derived secretomes of hyper-cellulolytic Penicillium janthinellum NCIM 1366 reveals the changes responsible for differences in hydrolytic performance - Sankar, Meena; Mathew, Reshma M.; Puthiyamadam, Anoop; Sreeja-Raju, Athiraraj; Christopher, Meera; Gokhale, Digambar Vitthal; Sukumaran, Rajeev K. (Bioresource Technology, 2023)
better hydrolytic performance along with a higher initial rate of reaction. Secretome analyses of the SSF and SmF enzymes using LC/MS-MS, indicated that while the type of proteins secreted were similar in both modes, the abundance of specific beta glucosidases, lytic polysaccharide monooxygenases and hemicellulolytic enzymes were very high in SSF resulting in efficient initiation, low accumulation of cellobiose and high initial reaction rates. Key enzymes that catalyse lignocellulose breakdown under SSF and SmF are therefore different and the fungus may be speculated to have regulation mechanisms that aid differential expression under different culti
Keywords: Cellulase; Solid -state fermentation

Early cellular events and potential regulators of cellulase induction in Penicillium janthinellum NCIM 1366 - Christopher, Meera; Sreeja-Raju, Athiraraj; Abraham, Amith; Gokhale, Digambar Vitthal; Pandey, Ashok; Sukumaran, Rajeev K. (Scientific Reports, 2023)
Cellulase production by fungi is tightly regulated in response to environmental cues, and understanding this mechanism is a key pre-requisite in the efforts to improve cellulase secretion. Based on UniProt descriptions of secreted Carbohydrate Active enZymes (CAZymes), 13 proteins of the cellulase hyper-producer Penicillium janthinellum NCIM 1366 (PJ-1366) were annotated as cellulases- 4 cellobiohydrolases (CBH), 7 endoglucanases (EG) and 2 beta glucosidases (BGL). Cellulase, xylanase, BGL and peroxidase activities were higher for cultures grown on a combination of cellulose and wheat bran, while EG was stimulated by disaccharides. Docking studies indicated that the most abundant BGL- Bgl2- has different binding sites for the substrate cellobiose and the product glucose, which helps to alleviate feedback inhibition, probably accounting for the low level of glucose tolerance exhibited. Out of the 758 transcription factors (TFs) differentially expressed on cellulose induction, 13 TFs were identified whose binding site frequencies on the promoter regions of the cellulases positively correlated with their abundance in the secretome. Further, correlation analysis of the transcriptional response of these regulators and TF-binding sites on their promoters indicated that cellulase expression is possibly preceded by up-regulation of 12 TFs and down-regulation of 16 TFs, which cumulatively regulate transcription, translation, nutrient metabolism and stress response.